Application of a Ruthenium-Catalyzed Allylation–Cycloisomerization Cascade to the Synthesis of (±)-Herbindole A - Thies, Nora; Stürminger, Martin; Haak, Edgar (Synlett, 2017)
A short and efficient total synthesis of the cytotoxic cyclopent[g]indole alkaloid (±)-herbindole A from dihydromesitylene has been achieved by incorporating a ruthenium-catalyzed allylation–cycloisomerization cascade reaction as the key step. The protocol has also been applied to the synthesis of the unnatural trans-epimer of the marine natural product.
Keywords: alkaloids; domino reaction; homogeneous catalysis; ruthenium; total synthesis.